2012
DOI: 10.1002/ps.3369
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of rodenticide resistance and zoonotic pathogens in Norway rats in Lower Saxony and Hamburg, Germany

Abstract: Zoonotic agents and genetically based resistance conferred by the Tyr139Cys polymorphism are both unevenly distributed in Lower Saxony. The study provides the basis for further studies focusing on districts with high levels of pathogens and resistance to assess the potential health risk of their combined occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…The occurrence of the Tyr139Cys genotype (German) seems to be more widespread, probably because this genotype was present earlier in the country compared with the Tyr139Phe genotype (French/Belgian). This seems to be similar to the situation in Germany, where the Tyr139Phe genotype has been encountered in one location, whereas the Tyr139Cys mutation seems to be widely distributed throughout north‐western Germany …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The occurrence of the Tyr139Cys genotype (German) seems to be more widespread, probably because this genotype was present earlier in the country compared with the Tyr139Phe genotype (French/Belgian). This seems to be similar to the situation in Germany, where the Tyr139Phe genotype has been encountered in one location, whereas the Tyr139Cys mutation seems to be widely distributed throughout north‐western Germany …”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it is assumed that the regions in which resistant R. norvegicus are found are expanding in the Netherlands, as has already happened in Germany . Figure shows that rats with either the Tyr139Cys or the Tyr139Phe genotype can be encountered in a significant part of the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…in different rat species. In Germany, Runge et al [30] found leptospiral DNA in 21% of the examined Norway rats ( Rattus norvegicus ), and in France, leptospiral renal carriage was shown in 34.7% of the studied Norway rats [31]. In Poland, renal carriage in Norway rats and black rats ( Rattus rattus ) ranged between 2 and 40%, depending on the region [32].…”
Section: Discussionmentioning
confidence: 99%
“…foraging), pest control is challenging . This problem has increased in certain regions on account of the emergence of rodenticide‐resistant rats …”
Section: Introductionmentioning
confidence: 99%